Promoting mental fitness in the context of active ageing policies: Comparative analysis of action programme objectives in eight countries - Romo Parra, Carmen; García-Martín, Miguel Ángel; Vera Balanza, María Teresa; Delgado Peña, José Jesús (Cuadernos de Trabajo Social, 2021)
In the context of an ageing European population there is increasing demand for policies and strategies aimed at maintaining or stimulating the cognitive abilities of older adults. Mental fitness programmes seek to maintain and promote the emotional and psychological wellbeing of older adults, enabling them to meet the demands of everyday life. Although many European countries have implemented programmes and services within a broad framework of active ageing, there are no standardised guidelines regarding how this should be done. In order to learn more about these programmes and services and provide useful information for decision making by policy makers we conducted a comparative study of the initiatives undertaken in eight different countries. Using qualitative content analysis we examined the stated objectives – in terms of attitudes, knowledge and abilities – of 116 programmes and services implemented across these countries. Overall, the results showed that ability objectives are much more common than are those focused on attitudes and knowledge. A more specific network analysis also provided information about how the sub-categories of each of the three kinds of objective are related to one another. The findings have practical implications for future planning of mental fitness programmes.
Keywords: Ageing; welfare policies; social programmes; psychosocial intervention; objectives